Ascariasis Detection with IgG4 Using ELISA in Adults at Pasie Nan Tigo Village Padang City - Anandila Maulina; Nuzulia Irawati; Fika Tri Anggraini (Journal of Agromedicine and Medical Sciences, 2022)
Ascariasis is still one of the most common STH infections found in school-age children, but adults may also suffer from this infection. This is due to the fact that the parasite is able to manipulate the host's immune response by increasing the IgG4 levels. The IgG4 technique is a new specific and sensitive method for detecting ascariasis. This study is aimed to determine the prevalence of ascariasis based on IgG4 levels using the ELISA method in adults at Pasie Nan Tigo Village, Padang City. This study is a descriptive study with a cross-sectional design that took place from July 2020 - May 2021 using a multistage random sampling technique where a total of 78 adult respondents in Pasie Nan Tigo Village. Blood samples were taken in order to check their IgG4 levels, using the ELISA at Prodia Laboratory. Data analysis was performed univariately with the purpose of finding the frequency distribution. The results of this study show that from the total of 78 respondents, the majority of age group found is 46-55 years old, namely 28 respondents, the majority of gender is female, namely 65 respondents, 57 respondents were positive for IgG4 where the most sufferers are 17-25 years old (88.9 %) and male (76.9%). The conclusion of this study is most of the respondents were in the age group of 46-55 years and women, there were more than half of the total respondents who detected ascariasis with the most sufferers being the age group of 17-25 years and men. Keywords: Ascaris lumbricoides, STH, T Cell Regulator